Monolayer polymer film and electronic device

A single-layer polymer film with crosslinked polyimide and controlled texture addresses the challenge of achieving low gloss and color in electronic devices, ensuring durability and resistance to etching processes.

JP7623183B2Active Publication Date: 2025-01-28DUPONT ELECTRONICS INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021055073
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2021-03-29
Publication Date
2025-01-28
Estimated Expiration
2041-03-29

AI Technical Summary

Technical Problem

Existing polyimide films for electronic devices face challenges in achieving both low gloss and low color simultaneously due to the dilution of pigment color and increased scattering, while multilayer structures risk exposure during etching processes, compromising durability and appearance.

Method used

A single-layer polymer film composed of crosslinked polyimide with specific refractive index, texture, and composition, including a gel distribution rate, colorant, and matte agents, is formulated to maintain low L*color and gloss, and is resistant to etching processes.

Benefits of technology

The single-layer polymer film achieves low gloss and color while maintaining durability and resistance to etching, suitable for electronic device applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623183000001
    Figure 0007623183000001
  • Figure 0007623183000002
    Figure 0007623183000002
  • Figure 0007623183000003
    Figure 0007623183000003
Patent Text Reader

Abstract

To provide single layer polymer films and electronic devices.SOLUTION: In a first aspect, a single layer polymer film includes 60 to 99 wt.% of a crosslinked polyimide, having a gel fraction in the range from 20 to 100% and a refractive index of 1.74 or less, and 1 to 40 wt.% of a colorant. A surface of the single layer polymer film has been textured and has a maximum roughness (Spv) of 6 μm or more, an L* color of 30 or less, and a 60° gloss of 15 or less. In a second aspect, a coverlay for a printed circuit board includes the single layer polymer film of the first aspect. In third and fourth aspects, processes are disclosed for forming a single layer polymer film including a crosslinked polyimide film including a dianhydride and a diamine.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The field of this disclosure is monolayer polymeric films, coverlays and electronics, and processes for forming same. [Background technology]

[0002] There is an increasing industry demand for polyimide films for electronics applications to have a matte appearance, have a specific color, be durable to handling and circuit processing, and, when used as a coverlay, provide protection against unwanted visual inspection of the electronic components protected by the coverlay. Single layer matte films do not have an L* color below 30, which provides the rich saturated color desired in the industry. Typically, as the amount of matting agent is increased, the color of the film is suppressed. The effect of increasing the surface roughness with the matting agent is a dilution of the pigment color, which appears lighter and less saturated. This is due to the dilution of the diffuse reflectance (where the pigment color is perceived) due to the increased scattering of the specular reflectance (white light). The rougher the surface, the lower the gloss and the higher the scattering of the specular reflectance. Thus, as the gloss decreases, the L* (lightness) typically increases. Adding more colorant does not decrease the L* color. Thus, it is difficult to achieve low gloss and low L* color simultaneously. To overcome these challenges, U.S. Patent Nos. 5,233,363, 5,293,222 and 5,366,633 use multilayer structures in which a thin polyimide layer loaded with a blend of matting agents, carbon black and submicron particles is adhered to a thicker base polyimide layer, resulting in a multilayer film that can achieve the desired combination of both low L* color and low gloss.

[0003] The success of multilayer coverlay in circuit fabrication depends on the thickness of the etch during pumice, desmear, and plasma processes. If the outer layer of the multilayer film is very thin, there is a risk that the outer layer of the film will be etched during these processes, exposing the base layer, resulting in significant changes in gloss and color. Therefore, the outer layer must be thick enough to withstand being removed during these processes. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] U.S. Pat. No. 9,469,781 [Patent Document 2] U.S. Patent No. 9,481,150 [Patent Document 3] U.S. Pat. No. 9,481,809 [Non-patent literature]

[0005] [Non-Patent Document 1] Y.Terui and S.Ando,J Polym Sci:Part B Polymer Physics,42,2354-2366(2004) Summary of the Invention [Problem to be solved by the invention]

[0006] As electronic devices and their electronic components become thinner and more compact, the challenge of forming a coverlay with both low gloss and low color becomes more difficult. In some cases, the need for thinner coverlays limits the use of matting agents that can have particle sizes comparable to the thickness of the film, further limiting the overall thickness of layers in multilayer coverlays. There is a demand for single-layer polymer films that have acceptable electrical properties (e.g., dielectric strength), mechanical properties, and durability to handling and circuit processing, while also providing a matte appearance, a rich, saturated color, and sufficient optical density to provide visual protection when used as a coverlay. The films also need to be more resistant to post-processing etching processes. [Means for solving the problem]

[0007] In a first embodiment, the monolayer polymer film comprises 60-99 wt. % of a crosslinked polyimide having a gel fraction in the range of 20-100% and a refractive index of 1.74 or less, and 1-40 wt. % of a colorant. The surface of the monolayer polymer film is textured and has a maximum roughness (Spv) of 6 μm or more, an L* color of 30 or less, and a 60° gloss of 15 or less.

[0008] In a second embodiment, a coverlay for a printed circuit board comprises the single layer polymeric film of the first embodiment.

[0009] In a third aspect, a process is disclosed for forming a monolayer polymer film comprising a crosslinked polyimide film comprising a dianhydride and a diamine. The dianhydride, diamine, or both the dianhydride and the diamine comprise cycloaliphatic monomers, aliphatic monomers, or both cycloaliphatic and aliphatic monomers. The polymer film has an L* color of 30 or less and a 60° gloss of 15 or less. The crosslinked polyimide film is (a) polymerizing a dianhydride and a diamine in the presence of a solvent to obtain a polyamic acid solution; (b) imidizing the polyamic acid solution to form a fully imidized solution; (c) adding a crosslinker and a colorant to the fully imidized solution; (d) casting the fully imidized solution onto a removable substrate having a textured surface with a maximum roughness (Spv) of 6 μm or greater to form a film; (e) crosslinking the polyimide while drying the film; and (f) by removing the monolayer polymeric film from the textured substrate.

[0010] In a fourth aspect, a process is disclosed for forming a monolayer polymer film comprising a crosslinked polyimide film comprising a dianhydride and a diamine. The dianhydride, diamine, or both the dianhydride and diamine comprise cycloaliphatic monomers, aliphatic monomers, or both cycloaliphatic and aliphatic monomers. The polymer film has an L* color of 30 or less and a 60° gloss of 15 or less. The crosslinked polyimide film comprises: (a) polymerizing a dianhydride and a diamine in the presence of a first solvent to obtain a polyamic acid solution; (b) imidizing the polyamic acid solution to form a first fully imidized solution; (c) precipitating the first fully imidized solution with an antisolvent; (d) filtering and drying the first fully imidized solution to obtain a solid polyimide resin; (e) dissolving the solid polyimide resin in a second solvent and adding a crosslinker and low conductivity carbon black to form a second fully imidized solution; (f) casting the second fully imidized solution onto a removable substrate having a textured surface with a maximum roughness (Spv) of 6 μm or greater to form a film; (g) crosslinking the polyimide while drying the film; and (h) formed by removing the monolayer polymeric film from the textured substrate.

[0011] The foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention, as defined in the appended claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In a first embodiment, the monolayer polymer film comprises 60-99 wt. % of a crosslinked polyimide having a gel fraction in the range of 20-100% and a refractive index of 1.74 or less, and 1-40 wt. % of a colorant. The surface of the monolayer polymer film is textured and has a maximum roughness (Spv) of 6 μm or more, an L* color of 30 or less, and a 60° gloss of 15 or less.

[0013] In one embodiment of the first aspect, the monolayer polymeric film further comprises a matting agent.

[0014] In another embodiment of the first aspect, the crosslinked polyimide comprises a dianhydride selected from the group consisting of aromatic dianhydrides, aliphatic dianhydrides, and mixtures thereof. In certain embodiments, the dianhydride is selected from the group consisting of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), cyclobutane dianhydride (CBDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), bisphenol A dianhydride (BPADA), 4,4'-oxydiphthalic anhydride (ODPA), bis(3,4-dicarboxyphenyl)sulfoxide dianhydride (DSDA), and hexahydro-4,8-ethano-1H,3H-benzo[1,2-c:4,5-c']difuran-1,3,5,7-tetrone (BODA), and mixtures thereof.

[0015] In yet another embodiment of the first aspect, the crosslinked polyimide comprises a diamine selected from the group consisting of aromatic diamines, aliphatic diamines, and mixtures thereof. In a particular embodiment, the diamine is selected from the group consisting of 1,6-hexamethylenediamine (HMD), trans-1,4-diaminocyclohexane (CHDA), 3-(4-aminophenyl)-1,1,3-trimethyl-5-indanamine (PIDA), isophoronediamine (IPDA), m-tolidine (MTB), 2,2'-bis(trifluoromethyl)benzidine (TFMB), m-phenylenediamine (MPD), 1,3-bis-(4-aminophenoxy)benzene (RODA), 2,2-bis-(4-[4-aminophenoxy]phenyl)propane (BAPP), and 3,4'-diaminodiphenylether (3,4-ODA), and mixtures thereof.

[0016] In yet another embodiment of the first aspect, the monolayer polymer film has a thickness in the range of 2 to 125 μm.

[0017] In yet another embodiment of the first aspect, the crosslinked polyimide has a refractive index of less than or equal to 1.69.

[0018] In a further embodiment of the first aspect, the colorant comprises low conductivity carbon black.

[0019] In a second embodiment, a coverlay for a printed circuit board comprises the single layer polymeric film of the first embodiment.

[0020] In a third aspect, a process is disclosed for forming a monolayer polymer film comprising a crosslinked polyimide film comprising a dianhydride and a diamine. The dianhydride, diamine, or both the dianhydride and the diamine comprise cycloaliphatic monomers, aliphatic monomers, or both cycloaliphatic and aliphatic monomers. The polymer film has an L* color of 30 or less and a 60° gloss of 15 or less. The crosslinked polyimide film is (a) polymerizing a dianhydride and a diamine in the presence of a solvent to obtain a polyamic acid solution; (b) imidizing the polyamic acid solution to form a fully imidized solution; (c) adding a crosslinker and a colorant to the fully imidized solution; (d) casting the fully imidized solution onto a removable substrate having a textured surface with a maximum roughness (Spv) of 6 μm or greater to form a film; (e) crosslinking the polyimide while drying the film; and (f) by removing the monolayer polymeric film from the textured substrate.

[0021] In a fourth aspect, a process is disclosed for forming a monolayer polymer film comprising a crosslinked polyimide film comprising a dianhydride and a diamine. The dianhydride, diamine, or both the dianhydride and the diamine comprise cycloaliphatic monomers, aliphatic monomers, or both cycloaliphatic and aliphatic monomers. The polymer film has an L* color of 30 or less and a 60° gloss of 15 or less. The crosslinked polyimide film comprises: (a) polymerizing a dianhydride and a diamine in the presence of a first solvent to obtain a polyamic acid solution; (b) imidizing the polyamic acid solution to form a first fully imidized solution; (c) precipitating the first fully imidized solution with an antisolvent; (d) filtering and drying the first fully imidized solution to obtain a solid polyimide resin; (e) dissolving the solid polyimide resin in a second solvent and adding a crosslinker and low conductivity carbon black to form a second fully imidized solution; (f) casting the second fully imidized solution onto a removable substrate having a textured surface with a maximum roughness (Spv) of 6 μm or greater to form a film; (g) crosslinking the polyimide while drying the film; and (h) formed by removing the monolayer polymeric film from the textured substrate.

[0022] In one embodiment of the process of the fourth aspect, after (e) and before (f), the second fully imidized solution is filtered to remove insoluble components of the solution.

[0023] In another embodiment of the process of the fourth aspect, the first and second solvents are the same or different.

[0024] While numerous aspects and embodiments have been described above, these are illustrative only and not limiting. After reading this specification, one skilled in the art will appreciate that other aspects and embodiments are possible without departing from the scope of the invention. Other features and advantages of the invention will be apparent from the following detailed description and claims.

[0025] In one embodiment, monolayer polymer films with crosslinked polyimides allow for the formation of very thin coverlays that are more resistant to etching than films using traditional coverlay materials. The use of soluble polyimides that are crosslinked after film formation results in monolayer polymer films with improved chemical resistance that maintain the low L* color and low gloss properties required for these films.

[0026] Depending on the context, as used herein, "diamine" is intended to mean (i) the unreacted form (i.e., the diamine monomer), (ii) the partially reacted form (i.e., the portion or portions of an oligomer or other polymer precursor derived or resulting from the diamine monomer), or (iii) the fully reacted form (the portion or portions of a polymer derived or resulting from the diamine monomer). The diamine can be functionalized at one or more sites, depending on the specific embodiment selected in the practice of the invention.

[0027] Indeed, the term "diamine" is not intended to be limiting (or to be taken literally) with respect to the number of amine moieties in the diamine component. For example, (ii) and (iii) above include polymeric materials that may have two, one, or zero amine moieties. Alternatively, the diamine can be functionalized with additional amine moieties (in addition to the amine moieties at the ends of the monomers that react with the dianhydride to grow the polymer chain). Such additional amine moieties could be used to crosslink the polymer or to provide other functional groups to the polymer.

[0028] Similarly, the term "dianhydride" as used herein is intended to mean a (complementary) component that reacts with a diamine, which can react in combination to form an intermediate that can then be cured into a polymer. Depending on the context, "anhydride" as used herein can refer not only to the anhydride moiety itself, but also to precursors of anhydride moieties, such as: (i) a pair of carboxylic acid groups, which can be converted to an anhydride by dehydration or similar types of reactions, or (ii) an acid halide (e.g., chloride) ester functional group (or any other functional group now known or developed in the future) that can be converted to an anhydride functional group.

[0029] Depending on the context, "dianhydride" can mean: (i) the unreacted form (i.e., the dianhydride monomers described in the paragraph above, regardless of whether the anhydride functionality is in true anhydride or precursor anhydride form), (ii) the partially reacted form (i.e., the portion or portions of an oligomer or other partially reacted or precursor polymer composition reacted from or resulting from the dianhydride monomer), or (iii) the fully reacted form (the portion or portions of a polymer derived from or resulting from the dianhydride monomer).

[0030] Dianhydrides can be functionalized with one or more sites, depending on the particular embodiment selected in the practice of the invention. Indeed, the term "dianhydride" is not intended to be limiting (or to be taken literally) with respect to the number of anhydride sites in the dianhydride component. For example, (i), (ii), and (iii) (in the paragraph above) include organic materials that may have two, one, or zero anhydride sites, depending on whether the anhydride is in a precursor state or in a reacted state. Alternatively, the dianhydride component can be functionalized with additional anhydride-type sites (in addition to the anhydride sites that react with the diamine to give the polymer). Such additional anhydride sites could be used to crosslink the polymer or to impart other functional groups to the polymer.

[0031] Any of several polyimide manufacturing processes can be used to prepare the monolayer polymer film. It would be impossible to discuss or describe all possible manufacturing processes useful in the practice of the present invention. It should be understood that the monomer system of the present invention can impart the advantageous properties described above in a variety of manufacturing processes. The compositions of the present invention can be manufactured as described herein, or can be readily manufactured in any of the many (possibly countless) ways by one of ordinary skill in the art, using any conventional or non-conventional manufacturing technique.

[0032] Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, suitable methods and materials are described herein.

[0033] When an amount, concentration, or other value or parameter is given as either a range, a preferred range, or a list of upper and lower preferred values, this should be understood to specifically disclose all ranges formed from any pair of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the ranges are separately disclosed. When a range of numerical values ​​is recited herein, unless otherwise stated, the range is intended to include the endpoints thereof and all integers and fractions within the range. The scope of the present invention is not intended to be limited to the specific values ​​recited when defining a range.

[0034] It should be understood that in describing particular polymers, applicants may refer to polymers by the monomers used to make them or the amounts of monomers used to make them. Such descriptions may not include the specific nomenclature or product-by-process terminology used to describe the final polymer, but any such reference to monomers and amounts should be interpreted to mean that the polymer is made from those monomers or amounts of monomers and the corresponding polymers and compositions thereof.

[0035] The materials, methods, and examples herein are illustrative only and are not intended to be limiting unless specifically stated. As used herein, the terms "comprises," "comprising," "includes," "including," "has," "having," or any other variation thereof, are intended to cover non-exclusive inclusions. For example, a method, process, article, or device that includes a list of elements is not necessarily limited to only those elements and may include other elements not expressly listed or inherent to such method, process, article, or device. Furthermore, unless expressly stated to the contrary, "or" means an inclusive or, not an exclusive or. For example, a condition A or B is satisfied by any one of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and A and B are both true (or exists).

[0036] Also, the use of "a" or "an" is used to describe elements and components of the present invention. This is done merely for convenience and to give a general sense of the invention. This description should be read to include one or at least one, and the singular also includes the plural unless it is clear that this is not meant.

[0037] Organic solvents Organic solvents useful in synthesizing the polymers of the present invention are preferably capable of dissolving the polymer precursor materials. Such solvents should also have a relatively low boiling point, such as less than 225°C, so that the polymer can be dried at moderate (i.e., more convenient and less costly) temperatures. Boiling points less than 210, 205, 200, 195, 190, or 180°C are preferred.

[0038] The solvent of the present invention can be used alone or in combination with other solvents (i.e., co-solvents). Useful organic solvents include N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), N,N'-dimethylformamide (DMF), dimethylsulfoxide (DMSO), tetramethylurea (TMU), diethylene glycol diethyl ether, 1,2-dimethoxyethane (monoglyme), diethylene glycol dimethyl ether (diglyme), 1,2-bis-(2-methoxyethoxy)ethane (triglyme), bis[2-(2-methoxyethoxy)ethyl)]ether (tetraglyme), γ-butyrolactone, and bis-(2-methoxyethyl)ether, tetrahydrofuran. In one embodiment, preferred solvents include N-methylpyrrolidone (NMP) and dimethylacetamide (DMAc).

[0039] Co-solvents may generally be used at about 5 to 50 weight percent of the total solvent; useful such co-solvents include xylene, toluene, benzene, "Cellosolve" (glycol ethyl ether), and "Cellosolve acetate" (hydroxyethyl acetate glycol monoacetate).

[0040] Diamine In one embodiment, suitable diamines for forming polyimides include aliphatic diamines such as 1,2-diaminoethane, 1,6-diaminohexane (HMD), 1,4-diaminobutane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane (DMD), 1,11-diaminoundecane, 1,12-diaminododecane (DDD), 1,16-hexadecamethylenediamine, 1,3-bis(3-aminopropyl)-tetramethyldisiloxane, trans-1,4-diaminocyclohexane (CHDA), isophoronediamine (IPDA), bicyclo[2.2.2]octane-1,4-diamine, and combinations thereof. Other aliphatic diamines suitable for the practice of the present invention include those having 6 to 12 carbon atoms, or combinations of long and short chain diamines, so long as both developability and flexibility are maintained. Long chain aliphatic diamines enhance flexibility.

[0041] In one embodiment, diamines suitable for forming polyimides include 2,2'-bis(trifluoromethyl)benzidine (TFMB), trifluoromethyl-2,4-diaminobenzene, trifluoromethyl-3,5-diaminobenzene, 2,2'-bis-(4-aminophenyl)-hexafluoropropane, 4,4'-diamino-2,2'-trifluoromethyldiphenyloxide, 3,3'-diamino-5,5'-trifluoromethyldiphenyloxide, 9.9'-bis(4-aminophenyl)fluorene, 4,4'-trifluoromethyl-2,2'-diaminobiphenyl, 4,4'-oxy-bis-[2-trifluoromethyl)benzenamine] (1,2,4-OBABTF), 4,4'-oxy-bis-[3-trifluoromethyl)benzenamine], 4,4'-thio-bis-[(2-trifluoromethyl)benzenamine], 4,4'-thiobis[(3-trifluoromethyl)benzenamine], 4,4'-sulfoxyl-bis-[(2-trifluoromethyl)benzenamine, 4,4'-sulfoxyl -Bis-[(3-trifluoromethyl)benzenamine], 4,4'-keto-bis-[(2-trifluoromethyl)benzenamine], 1,1-bis[4'-(4"-amino-2"-trifluoromethylphenoxy)phenyl]cyclopentane, 1,1-bis[4'-(4"-amino-2"-trifluoromethylphenoxy)phenyl]cyclohexane, 2-trifluoromethyl-4,4'-diaminodiphenyl ether; 1,4-(2'-trifluoromethyl-4',4"-diaminodiphenoxy)-benzene, 1,4-bis(4'-aminophenoxy) )-2-[(3',5'-ditrifluoromethyl)phenyl]benzene, 1,4-bis[2'-cyano-3'("4-aminophenoxy)phenoxy]-2-[(3',5'-ditrifluoromethyl)phenyl]benzene (6FC-diamine), 3,5-diamino-4-methyl-2',3',5',6'-tetrafluoro-4'-trifluoromethyldiphenyloxide, 2,2-bis[4'(4"-aminophenoxy)phenyl]phthalein-3',5'-bis(trifluoromethyl)anilide (6FADAP), and 3,3',5,5'-tetrafluoro-4-methyl-2',3',5',6'-tetrafluoro-4'-trifluoromethyldiphenyloxide. Further examples include fluorinated aromatic diamines such as fluoro-4,4'-diamino-diphenylmethane (TFDAM). In a particular embodiment, the fluorinated diamine is 2,2'-bis(trifluoromethyl)benzidine (TFMB). In one embodiment, the fluorinated aromatic diamine can be present in a range of 40 to 95 mole percent based on the total diamine components of the polyimide. In a more specific embodiment, the fluorinated aromatic diamine can be present in a range of 50 to 75 mole percent based on the total diamine components of the polyimide.

[0042] In one embodiment, p-phenylenediamine (PPD), m-tolidine (MTB), m-phenylenediamine (MPD), 3-(4-aminophenyl)-1,1,3-trimethyl-5-indanamine (PIDA), 2,5-dimethyl-1,4-diaminobenzene, 2,5-dimethyl-1,4-phenylenediamine (DPX), 2,2-bis-(4-aminophenyl)propane, 1,4-naphthalenediamine, 1,5-naphthalenediamine, 4,4'-diaminobiphenyl, 4,4"-diaminoter ... ,4'-Diaminobenzanilide, 4,4'-diaminophenylbenzoate, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenylmethane (MDA), 4,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, bis-(4-(4-aminophenoxy)phenyl sulfone (BAPS), 4,4'-bis-(aminophenoxy)biphenyl (BAPB), 4,4'-diaminodiphenyl ether (ODA), 3,4'-diamino Nodiphenyl ether (3,4-ODA), 4,4'-diaminobenzophenone, 4,4'-isopropylidenedianiline, 2,2'-bis-(3-aminophenyl)propane, N,N-bis-(4-aminophenyl)-n-butylamine, N,N-bis-(4-aminophenyl)methylamine, 1,5-diaminonaphthalene, 3,3'-dimethyl-4,4'-diaminobiphenyl, m-aminobenzoyl-p-aminoanilide, 4-aminophenyl-3-aminobenzoate, N,N-bis-(4-aminophenyl)methylamine, Any number of additional diamines can be used in forming the polyimide, including bis-(β-amino-t-butyl)toluene, bis-(p-β-amino-t-butylphenyl)ether, p-bis-2-(2-methyl-4-aminopentyl)benzene, m-xylylenediamine, and p-xylylenediamine.

[0043] Other useful diamines include 1,2-bis-(4-aminophenoxy)benzene, 1,3-bis-(4-aminophenoxy)benzene (RODA), 1,2-bis-(3-aminophenoxy)benzene, 1,3-bis-(3-aminophenoxy)benzene, 1-(4-aminophenoxy)-3-(3-aminophenoxy)benzene, 1,4-bis-(4-aminophenoxy)benzene, 1,4-bis-(3-aminophenoxy)benzene, 1-(4-aminophenoxy)-4-(3-aminophenoxy)benzene, 2,2-bis-(4-[4-aminophenoxy]phenyl)propane (BAPP), 2,2'-bis-(4-phenoxyaniline)isopropylidene, 2,4,6-trimethyl-1,3-diaminobenzene, and 2,4,6-trimethyl-1,3-diaminobenzene.

[0044] dianhydride In one embodiment, any number of suitable dianhydrides can be used in forming the polyimide. The dianhydrides can be used in their tetraacid form (or as mono-, di-, tri- or tetraesters of the tetraacid) or as their diester acid halides (chlorides). However, in some embodiments, the dianhydride forms can be preferred because they are generally more reactive than the acids or esters.

[0045] Examples of suitable dianhydrides include 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 2-(3',4'-dicarboxyphenyl)5,6-dicarboxybenzimidazole dianhydride, 2-(3',4'-dicarboxyphenyl)5,6-dicarboxybenzoxazole dianhydride, 2-(3',4'-dicarboxyphenyl)5,6-dicarboxybenzothiazol dianhydride, and 2-(3',4'-dicarboxyphenyl)5,6-dicarboxybenzothiazol dianhydride. 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, bicyclo-[2,2,2]-octene-(7)-2,3,5,6-tetracarboxylic-2,3,5,6-dianhydride, 4,4'-thio-diphthalic anhydride, bis(3,4-dicarboxyphenyl)sulfonyl 4,4'-oxydiphthalic anhydride (ODPA), bis(3,4-dicarboxyphenyl)thioether dianhydride, bisphenol A dianhydride (BPADA), bis(3,4-dicarboxyphenyl)sulfoxide dianhydride (DSDA), bis(3,4-dicarboxyphenyloxadiazole-1,3,4)p-phenylene dianhydride, bis(3,4-dicarboxyphenyl)2,5-oxadiazole 1,3,4-dianhydride, bis2,5-(3',4'-dicarboxydiphenylether)1,3,4-oxadiazole dianhydride, 4,4'-oxydiphthalic anhydride (ODPA), bis(3,4-dicarboxyphenyl)thioether dianhydride, bisphenol A dianhydride (BPADA), bis Phenol S dianhydride, bis-1,3-isobenzofuran dione, 1,4-bis(4,4'-oxyphthalic anhydride)benzene, bis(3,4-dicarboxyphenyl)methane dianhydride, cyclopentadienyl tetracarboxylic dianhydride, cyclopentane tetracarboxylic dianhydride, ethylene tetracarboxylic dianhydride, perylene 3,4,9,10-tetracarboxylic dianhydride, pyromellitic dianhydride (PMDA), tetrahydrofuran tetracarboxylic dianhydride, 1,3-bis-(4,4'-oxydiphthalic anhydride)benzene, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-tetrachloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, phenanthrene-1,8,9,10-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, benzene-1,2,3,4-tetracarboxylic dianhydride, and thiophene-2,3,4,5-tetracarboxylic dianhydride.

[0046] In one embodiment, suitable dianhydrides may include alicyclic dianhydrides such as cyclobutane dianhydride (CBDA), cyclohexane dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), hexahydro-4,8-ethano-1H,3H-benzo[1,2-c:4,5-c']difuran-1,3,5,7-tetrone (BODA), 3-(carboxymethyl)-1,2,4-cyclopentanetricarboxylic 1,4:2,3-dianhydride (TCA), and meso-butane-1,2,3,4-tetracarboxylic dianhydride.

[0047] In one embodiment, suitable dianhydrides for forming polyimides can include fluorinated dianhydrides such as 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) and 9,9-bis(trifluoromethyl)-2,3,6,7-xanthenetetracarboxylic dianhydride.

[0048] Crosslinking Agent In one embodiment, a crosslinking agent is used in the polymer film. By crosslinking the polyimide, the polymer film can have improved mechanical properties and improved chemical resistance. Crosslinking agents include Jeffamine® D-230, Jeffamine® D-400, Jeffamine® D-2000, Jeffamine® D-2010, Jeffamine® D-4000, Jeffamine® ED-600, Jeffamine® ED-900, Jeffamine® D-2003, Jeffamine® EDR-148, Jeffamine® THF-100, Jeffamine® THF-170, Jeffamine® SD ... 001, Jeffamine® D-205, and Jeffamine® RFD-270, secondary amines such as piperazine, N,N'-diisopropylethylenediamine, N,N'-diisopropyl-1,3-propanediamine, and N,N'-dimethyl-1,3-propanediamine, and triamines such as 2,4,6-triaminopyrimidine (TAP), melamine, diethylenetriamine, Jeffamine® T-403, Jeffamine® T-3000, Jeffamine® T-5000, etc. In addition, as mentioned above, many diamines that can be used as diamine monomers for polyimides can also be useful as crosslinkers.

[0049] Coloring agent In one embodiment, the polymer film comprises about 1 to about 40 weight percent colorant, such as a pigment or dye. In some embodiments, the polymer film comprises about 1 to about 40 weight percent of a mixture of pigments and dyes. In some embodiments, the polymer film comprises between and between any two of the following: 1, 5, 10, 15, 20, 25, 30, 35, and 40 weight percent colorant.

[0050] Any pigment (or combination of pigments) may be satisfactorily used in the practice of the present invention. In some embodiments, useful pigments include, but are not limited to, the following: barium lemon yellow, cadmium yellow lemon, cadmium yellow light, cadmium yellow middle, cadmium yellow orange, scarlet lake, cadmium red, cadmium vermilion, alizarin crimson, permanent magenta, Van Dyke brown, raw umber green, or burnt umber. In some embodiments, useful black pigments include cobalt oxide, Fe-Mn-Bi black, Fe-Mn oxide spinel black, (Fe,Mn)2O3 black, chromite black spinel, lamp black, bone black, bone ash, bone char, hematite, black iron oxide, mica iron oxide, black complex inorganic color pigments (CICP), (Ni,Mn,Co)(Cr,Fe)2O4 black, aniline black, perylene black, anthraquinone black, chrome green black hematite, chrome iron oxide, Pigment Green 17, Pigment Black 26, Pigment Black 27, Pigment Black 28, Pigment Brown 29, Pigment Brown 35, Pigment Black 30, Pigment Black 32, Pigment Black 33, or mixtures thereof.

[0051] In some embodiments, the pigment is lithopone, zinc sulfide, barium sulfate, cobalt oxide, yellow iron oxide, orange iron oxide, red iron oxide, brown iron oxide, hematite, black iron oxide, mica iron oxide, chromium (III) green, ultramarine blue, ultramarine violet, ultramarine pink, iron cyanide blue, cadmium pigments, or lead chromate pigments.

[0052] In some embodiments, the pigment is a complex inorganic color pigment (CICP), such as a spinel pigment, a rutile pigment, a zircon pigment, or a bismuth vanadate yellow. In some embodiments, useful spinel pigments include, but are not limited to, Zn(Fe,Cr)2O4 brown, CoAl2O4 blue, Co(AlCr)2O4 blue-green, Co2TiO4 green, CuCr2O4 black, or (Ni,Mn,Co)(Cr,Fe)2O4 black. In some embodiments, useful rutile pigments include, but are not limited to, Ti-Ni-Sb yellow, Ti-Mn-Sb brown, Ti-Cr-Sb buff, zircon pigment, or bismuth vanadate yellow.

[0053] In another embodiment, the pigment is an organic pigment. In some embodiments, useful organic pigments include, but are not limited to, aniline black (pigment black 1), anthraquinone black, monoazo type, diazo type, benzimidazolone, diarylide yellow, monoazo yellow salt, dinitronine orange, pyrazolone orange, azo red, naphthol red, azo condensation pigment, lake pigment, copper phthalocyanine blue, copper phthalocyanine green, quinacridone, diaryl pyrrolopyrrole, aminoanthraquinone pigment, dioxazine, isoindolinone, isoindoline, quinophthalone, phthalocyanine pigment, idanthrone pigment, pigment violet 1, pigment violet 3, pigment violet 19, or pigment violet 23. In yet another embodiment, the organic pigment is a vat dye pigment, such as, but not limited to, perylene, perylene black, perinone, or thioindigo. A uniform dispersion of isolated individual pigment particles (agglomerates) tends to produce uniform color intensity. In some embodiments, the pigment is milled. In some embodiments, the average particle size of the pigment includes between (and optionally between) any two of the following sizes: 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0 μm. In some embodiments, luminescent (fluorescent or phosphorescent) or lustrous pigments can be used alone or in combination with other pigments or dyes.

[0054] In one embodiment, the colorant may include low-conductivity carbon black. In some embodiments, the colorant includes between and any two of the following: 1, 5, 10, 15, and 20 weight percent low-conductivity carbon black. In yet another embodiment, the colorant includes from about 2 to about 9 weight percent low-conductivity carbon black.

[0055] Low conductivity carbon black is intended to mean channel type black, furnace black or lamp black. In some embodiments, the low conductivity carbon black is a surface oxidized carbon black. One way to assess the extent of surface oxidation (of carbon black) is to measure the heat loss of the carbon black. Heat loss can be measured by calculating the weight loss when baked at 950° C. for 7 minutes. Generally, highly surface oxidized carbon black (high heat loss) is easily dispersible in polyamic acid solutions (polyimide precursors) that can then be imidized into the (well-dispersed) filled polyimide base polymers of the present disclosure. It is believed that if the carbon black particles (aggregates) do not contact each other, electron tunneling, electron hopping or other electron flow mechanisms are generally suppressed, resulting in low conductivity. In some embodiments, the low conductivity carbon black has a heat loss of 1% or more. In some embodiments, the low conductivity carbon black has a heat loss of 5, 9 or 13% or more. In some embodiments, the furnace black can be surface treated to increase the heat loss. Typically, low conductivity carbon black has a pH of less than about 6.

[0056] A uniform dispersion of isolated carbon black particles (agglomerates) not only reduces the conductivity, but additionally tends to produce uniform color intensity. In some embodiments, the low conductivity carbon black is milled. In some embodiments, the average particle size of the low conductivity carbon black includes between (and optionally between) any two of the following sizes: 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0 μm.

[0057] Matting agent In one embodiment, the polymer film comprises about 0.5 to about 20 weight percent matting agent selected from the group consisting of silica, alumina, zirconia, boron nitride, barium sulfate, polyimide particles, calcium phosphate, talc, or mixtures thereof. In some embodiments, the polymer film comprises between and between any two of the following: 0.5, 1, 5, 10, 15, and 20 weight percent matting agent. In one embodiment, the matting agent has a particle size ranging from about 2 to about 10 μm, or from about 3 to about 9 μm, or from about 5 to about 7 μm.

[0058] Submicron Particles In one embodiment, the polymer layer comprises up to about 39% by weight of at least one submicron particle, such as submicron fumed metal oxide (also known as pyrogenic metal oxide) or submicron colloidal metal oxide or mixtures thereof. In some embodiments, the submicron fumed metal oxide is fumed alumina, fumed silica, or mixtures thereof. The addition of the submicron fumed metal oxide surprisingly lowers the amount of colorant (such as submicron carbon black) required in the polymer film to produce a film with an L* color of less than about 30. Since submicron fumed alumina and fumed silica can be whitish or hazy by themselves in PI films, it was not expected that their addition would actually reduce the amount of colorant required to produce a rich, saturated color. It is also surprising that other submicron metal oxides do not have the same effect. In one embodiment, the polymer layer comprises up to about 20% by weight, or up to about 10% by weight, of at least one submicron particle. In one embodiment, the submicron particle has a particle size of less than about 1 μm. In one embodiment, the submicron particles have a particle size ranging from about 0.01 to about 1 μm, or from about 0.05 to about 0.5 μm.

[0059] The particle size of the submicron particles, carbon black and matting agents can be measured in the slurry by laser diffraction using a particle size analyzer such as an LA-930 (Horiba, Instruments, Inc., Irvine Calif.), Mastersizer 3000 (Malvern Instruments, Inc., Westborough, Mass.) or LS-230 (Beckman Coulter, Inc., Indianapolis, Ind.). However, due to the tendency of submicron particles to agglomerate, it may be more accurate to measure the particle size of these milled slurries by observation with an optical microscope.

[0060] Single-layer polymer film As used herein, the term "monolayer polymer film" refers to a layer of polymer film having essentially homogeneous composition throughout the layer, such that the monomers used to form the polymer are present throughout the thickness of the layer, and any fillers, such as matting agents, carbon black, and submicron particles, are distributed throughout the thickness of the layer. A monolayer polymer film is essentially homogeneous, but may have some gradient in the composition of the layer over a region or throughout its thickness, and especially at the surface of the film. In contrast, a polymer film whose composition changes distinctly over the region or thickness of the film would not be a monolayer polymer film. For example, a polyimide film having a core layer of one composition and a thin outer layer of a different composition (such as different monomers used to form the polymer of the outer layer or different fillers in the outer layer) would not be a monolayer polymer.

[0061] In one embodiment, the single layer polymer film may include a polyimide, which may be made by combining a diamine and a dianhydride (monomer or other polyimide precursor form) with a solvent to form a polyamic acid (also called polyamic acid) solution. The dianhydride and diamine may be combined in a molar ratio of about 0.90 to 1.10. The molecular weight of the polyamic acid formed therefrom may be adjusted by adjusting the molar ratio of the dianhydride to the diamine.

[0062] Useful methods for making polymeric films comprising polyimides include: (a) The diamine and dianhydride components are premixed together and then added portion-wise to the solvent while the mixture is being stirred. (b) A method in which the solvent is added to a stirred mixture of the diamine and dianhydride components (as opposed to (a) above). (c) A method in which the diamine is dissolved exclusively in a solvent and then the dianhydride is added thereto in a ratio which makes it possible to control the reaction rate. (d) A method in which the dianhydride component is dissolved exclusively in a solvent and then the amine component is added thereto in a ratio which makes it possible to control the reaction rate. (e) A process in which the diamine and dianhydride components are dissolved separately in a solvent and then the solutions are mixed in a reactor. (f) A process in which a polyamic acid containing an excess of an amine component and another polyamic acid containing an excess of a dianhydride component are preformed and then reacted with one another in a reactor in such a way that non-random or block copolymers can be made in particular. (g) A specific portion of the amine and dianhydride components are reacted first and then the remaining diamine component is reacted, or vice versa. (h) A process in which the ingredients are added partially or wholly in any order into any part or all of the solvent, and further in which any or all of the ingredients may also be added as solutions in any or all of the solvent. (i) One of the dianhydride components is first reacted with one of the diamine components to give a first polyamic acid, then another dianhydride component is reacted with another amine component to give a second polyamic acid, and the amic acids are then combined in any of several ways.

[0063] In one embodiment, the polyamic acid solution can be combined with a conversion chemical such as: (i) one or more dehydrating agents, such as fatty acid anhydrides (such as acetic anhydride) and / or aromatic acid anhydrides, and (ii) one or more catalysts, such as aliphatic tertiary amines (such as triethylamine), aromatic tertiary amines (such as dimethyldiamine), and heterocyclic tertiary amines (such as pyridine, α, β and γ picolines (2-methylpyridine, 3-methylpyridine, 4-methylpyridine), isoquinoline, etc.). The dehydrating agents, which are anhydrides, are often used in molar excess compared to the amount of amic acid groups in the polyamic acid. The amount of acetic anhydride used is typically about 2.0 to about 4.0 moles per equivalent (repeating unit) of polyamic acid. Generally, an equivalent amount of tertiary amine catalyst is used.

[0064] In one embodiment, the conversion chemical can be an imidization catalyst. The use of an imidization catalyst can help to lower the imidization temperature and shorten the imidization time. Typical imidization catalysts can range from bases such as imidazole, 1-methylimidazole, 2-methylimidazole, 1,2-dimethylimidazole, 2-phenylimidazole, benzimidazole, isoquinoline, or substituted pyridines (such as methylpyridine, lutidine, and trialkylamines). A combination of tertiary amines and acid anhydrides can be used. These dehydrating agents that can function as cocatalysts include acetic anhydride, propionic anhydride, n-butyric anhydride, benzoic anhydride, and the like. The ratio of these catalysts and their concentrations in the polyamic acid solution will affect the imidization kinetics.

[0065] In one embodiment, the polyamic acid solution can be heated, optionally in the presence of an imidization catalyst, to partially or fully imidize the polyamic acid and convert it to a polyimide. Temperature, time, and the concentration and selection of the imidization catalyst can affect the degree of imidization of the polyamic acid solution. Preferably, the solution should be fully imidized. In one embodiment, for a fully polyimide solution, greater than about 85%, greater than about 90%, or greater than about 95% of the amic acid groups are converted to polyimide as determined by infrared spectroscopy.

[0066] In one embodiment, sufficient polyimide solutions are formed using monomers (diamines or dianhydrides) that have structural characteristics important for solubility, including, but not limited to, flexible linkages such as aliphatic spacers, ethers, thioethers, substituted amines, amides, esters, and ketones, weak intermolecular interactions, bulky substituents, non-resonant, non-linear, and asymmetric. Examples of diamines incorporating some of these characteristics are aliphatic diamines such as HMD, CHDA, and IPDA, and aromatic diamines such as MTB TFMB, MPD, RODA, BAPP, and 3,4-ODA. Examples of dianhydrides incorporating some of these characteristics are 6FDA, BPADA, ODPA, DSDA, and BODA.

[0067] In one embodiment, the solvated mixture (fully imidized solution) can be mixed with a crosslinker and a colorant, such as a pigment or dye, and then cast to form a single layer polyimide film. In one embodiment, the colorant can be low conductivity carbon black. In another embodiment, the solvated mixture (first fully imidized solution) can be precipitated with an anti-solvent, such as water or an alcohol (e.g., methanol, ethanol, isopropyl alcohol). In one embodiment, the precipitate can be washed to remove the catalyst. After washing, the precipitate can be thoroughly dried, but does not need to be completely dried. The polyimide precipitate can be redissolved in a second solvent, such as methyl isobutyl ketone (MIBK), methyl ethyl ketone (MEK), tetrahydrofuran (THF), cyclopentanone, ethyl acetate, acetone, DMAc, NMP, and mixtures thereof, to form a second fully imidized solution (cast solution). A crosslinker and a colorant can be added to the second fully imidized solution, and then cast to form a single layer polymer film. In one embodiment, the monolayer polymer film comprises in the range of about 80 to about 99 weight percent crosslinked polyimide. In some embodiments, the polymer film comprises between and including any two of the following: 80, 85, 90, 95, and 99 weight percent crosslinked polyimide. In yet other embodiments, the polymer film comprises from about 91 to about 98 weight percent crosslinked polyimide.

[0068] Crosslinking of polyimides can be determined by a variety of methods. In one embodiment, the gel fraction of polyimides can be determined by comparing the weight of dried films before and after crosslinking and using the equilibrium swelling method. In one embodiment, crosslinked polyimides can have gel fractions ranging from about 20 to about 100%, or about 40 to about 100%, or about 50 to about 100%, or about 70 to about 100%, or about 85 to about 100%. In one embodiment, crosslinked networks can be identified using rheological methods. Oscillatory time sweep measurements at specific strains, frequencies, and temperatures can be used to confirm the formation of crosslinked networks. Initially, the loss modulus (G'') value is higher than the storage modulus (G') value, indicating that the polyimide solution behaves like a viscous liquid. Over time, the formation of a crosslinked polyimide network is evidenced by the intersection of the G' and G'' curves. The crossover, called the "gel point", represents when the elastic component predominates over the viscous component and the polymer begins to behave like an elastic solid.

[0069] In one embodiment, the fully imidized polyimide solution can be cast or coated onto a support such as an endless belt or rotating drum to form a film. Alternatively, it can be cast onto a polymeric support such as polyethylene terephthalate (PET) film, other forms of Kapton® polyimide film (e.g., Kapton® HN or Kapton® OL film) or other polymeric support. In one embodiment, the support or support layer can be textured, such as a textured PET substrate. The fully imidized solution can then be converted into a film by heating to crosslink the polyimide and partially or completely remove the solvent. The film is heated at a low temperature to initiate polyimide crosslinking and partially dry the polyimide film. Typically, temperatures below about 100° C. are used for initial drying and crosslinking. The film is then heated at an elevated temperature, up to about 300° C., to complete the polyimide crosslinking and further remove the solvent. In some aspects of the invention, the film is peeled off the support before it is completely dried. The final drying step can be performed using a dimensional support for the film. In other aspects, the film is heated directly on the support.

[0070] In one embodiment, the monolayer polymer film comprises a polyimide having a low refractive index, such as less than about 1.74, or less than about 1.69, or less than about 1.60. Reducing the refractive index of the polyimide allows for the formation of a monolayer polymer film with both low L* and low gloss. Conventional polyimides exhibit a fairly high refractive index (RI) due to their higher content of aromatic rings and imide structures than other common optical polymers. However, their poor transparency in the visible region is a serious obstacle to light trapping and increases reflection from the film surface. The optical absorption of polyimides in the visible region is mainly caused by intra- and intermolecular charge transfer (CT) interactions between the electron-donating diamine and the electron-accepting dianhydride moieties. In one embodiment, the average refractive index of the material, nav, can be estimated by the Lorentz-Lorentz equation:

[0071]

number

[0072] (where αav is the average molecular polarizability, Vint is the specific volume of the repeating unit, ρ is the density, NA is Avogadro's number, and M is the molecular weight). This formula can be expressed as follows:

[0073]

number

[0074] where Kp is the molecular packing factor and Vvdw is the van der Waals volume of the molecule (see Non-Patent Document 1). One way to minimize the refractive index of a polymer blend based on this equation is by minimizing the contribution from the αav / Vvdw ratio. The variables in this ratio can be calculated from empirical, semi-empirical, or ab initio principles. This calculated ratio can be used to select or eliminate monomers to target a low refractive index. The objective is to reduce the polarizability of the polyimide chain and thus the refractive index of the polymer. The polarizability of the polymer can be reduced by the introduction of electron-withdrawing fluorine atoms or fluorinated substituents, the incorporation of alicyclic moieties, and the modification of the molecular backbone with meta-substituted structures and bulky side groups.

[0075] In one embodiment, the monolayer polymer film can have an L* of about 30 or less and a 60° gloss (60GU) of about 15 or less. In one embodiment, the monolayer polymer film can have an L* of about 25 or less, or about 20 or less. In one embodiment, the monolayer polymer film can have a 60° gloss of about 10 or less, or about 8 or less, or about 6 or less.

[0076] The thickness of the monolayer polymer film can be adjusted depending on the intended purpose or end use specifications of the film. In one embodiment, the monolayer polymer film has a total thickness in the range of about 2 to about 125 μm, or about 4 to about 50 μm, or about 5 to about 20 μm.

[0077] In one embodiment, the monolayer polymer film can be textured using mechanical or chemical means. In one embodiment, mechanical texturing can include a process that physically removes a portion of the film surface, such as sandblasting or laser ablation. In one embodiment, for sandblasting, the monolayer polymer film can be textured by spraying fine sand onto the surface of the film in an abrasive blasting (centrifugal blasting) process, where a rotating impeller sprays the sand using centrifugal force. In one embodiment, the texturing can be provided by embossing or imprinting the texture onto the film surface. In one embodiment, in imprinting, the monolayer polymer film is textured by casting the film onto a textured surface, where the texturing is transferred to the polymer film surface. In one embodiment, chemical texturing can be imparted by lithography.

[0078] In one embodiment, the textured film can have both low L* color and low gloss, even if the film does not contain a matting agent. In one embodiment, the monolayer polymer film with a textured surface can have a maximum roughness (Spv) of about 6 μm or more, an L* of about 30 or less, and a 60° gloss (60GU) of about 15 or less. In one embodiment, the monolayer polymer film with a textured surface can have an Spv of about 7 μm or more, or about 8 μm or more. In one embodiment, the monolayer polymer film with a textured surface can have an L* of about 25 or less, or about 20 or less. In one embodiment, the monolayer polymer film with a textured surface can have a 60° gloss of about 10 or less, or about 8 or less, or about 6 or less. In one embodiment, both sides of the monolayer polymer film can have a textured surface.

[0079] Purpose In one embodiment, the single layer polymer film can be used in electronic applications such as coverlay for printed circuit boards or other electronic components in electronic devices to provide protection from physical damage, oxidation, and other contaminants that can adversely affect the functionality of the electronic components. Very thin coverlays of single layer polymer films using crosslinked polyimides can be more chemically resistant, resistant to etching during pumice, desmear, and plasma processes used in circuit fabrication, and maintain good optical properties.

[0080] The advantageous properties of this invention can be appreciated by reference to the following examples, which illustrate but do not limit the invention. All parts and percentages are by weight unless otherwise specified. EXAMPLES

[0081] Test Method CIE L*, a*, b* colors Color measurements were made using a ColorQuest® XE Dual Beam Spectrophotometer (Hunter Associates Laboratory, Inc., Reston, VA) in reflectance, specular reflection inclusive mode. The instrument was standardized before each use. Color data from the instrument was reported in the CIELAB 10° / D65 system as L*, a*, b*. An L* value of 0 is pure black, while an L* value of 100 is pure white. Typically, a difference in L* value of 1 unit can be discerned by eye.

[0082] Refractive index Refractive index measurements were made using a Metricon® model 2010 prism coupler (Metricon Corporation, Pennington, NJ) using a laser wavelength of 633 nm (632.8 nm). The instrument was standardized before each use. Refractive index measurements were made in TE mode to report the in-plane refractive index of the film.

[0083] Gel fraction The gel fraction of polyimides was measured using the Soxhlet extraction method. The polymer film sample was placed on a glass thimble, which was placed in the main chamber of the Soxhlet extractor resting on a round-bottom flask filled with nitrogen-purged solvent. The extraction solvent (DMAc) was continuously circulated through the sample by boiling and condensing. After sufficient heat was applied to the round-bottom flask, the solvent in vapor form was transferred to the main chamber of the Soxhlet extractor and condensed. After reaching an overflow level, the solvent was allowed to flow back into the round-bottom flask through a siphon tube.

[0084] Approximately 2 x 3 inches of polymer film was used. Film samples were wiped clean with acetone, air dried before being placed in a glass thimble, weighed, and creased. The temperature of the DMAc (approximately 300 ml) was set to 165-175°C and extraction was carried out over a period of at least 7 hours. The samples were then removed from the apparatus, dried on a hot plate at 50°C for up to 1 hour, and placed in an oven at 120°C. The oven was heated from 120 to 250°C (16°C / min) and then held at 250°C for 20 minutes. After 20 minutes at 250°C, the films were removed from the oven "hot", allowed to cool in air, and the samples were re-weighed. Fresh solvent was used for each sample.

[0085] 60° gloss 60° gloss (60GU) was measured using a Micro-TRI-Gloss glossmeter (BYK-Gardner USA, Columbia, MD), which was calibrated before each use.

[0086] particle size The particle size of the filler particles in the slurry was measured by laser diffraction using a particle size analyzer (Mastersizer 3000, Malvern Instruments, Inc., Westborough, Mass.) DMAc was used as the dispersion medium.

[0087] Surface roughness Surface roughness was measured over an area of ​​167 × 167 μm (0.28 mm2) using a ZeGage™ Pro 3D optical profiler (Zygo Corp., Middlefield, CT). Maximum roughness (Spv, Sz, or Rz) is the sum of the maximum peak height (Sp) and maximum valley depth (Sv) of the surface being measured, Spv = Sp + Sv.

[0088] Low Conductivity Carbon Black A carbon black solution was prepared consisting of 90 wt. % DMAc and 10 wt. % carbon black powder (Special Black 4, SB4, Orion Engineered Carbons LLC, Kingwood, TX). The ingredients were thoroughly mixed using a hand-held high shear mixer.

[0089] Comparative Example 1 and Example 1 In Comparative Example 1 and Example 1 (CE1 and E1), a soluble thermoplastic polyimide (Matrimid® 9725, Huntsman Corp., The Woodlands, TX) was used as a dry powder with a monomer composition of 3,3',4,4'-benzophenonetetracarboxylic dianhydride / / 3-(4-aminophenyl)-1,1,3-trimethyl-5-indamine (BTDA1.0 / / PIDA1.0).

[0090] For CE1, 5 g of dry polymer resin was added to 17.4 g of dimethylacetamide (DMAc, HPLC grade) and mixed in a centrifugal planetary mixer (THINKY USA, Laguna Hills, CA) to obtain a solution. The solution was degassed using a centrifugal planetary mixer for 10 minutes at 2000 rpm to outgas the polymer. 2.5 g of a 10 wt % solution of SB4 carbon (Orion Engineered Carbons) in DMAc was added to the polyimide solution along with a release agent to facilitate removal of the film from the cast substrate. The solution was mixed using a centrifugal planetary mixer for 2 minutes at 2200 rpm, followed by degassing for 5 minutes at 2000 rpm.

[0091] The solutions were cast onto a matte PET substrate (Kaisei Industries, Inc., Japan) at 25°C to produce 1-2 mil cured films. The films on the matte PET substrate were heated at 80°C for 15 min, then lifted off the matte PET surface and mounted in an 8 x 12 inch frame. The mounted films were placed in an oven. The oven was heated from 120 to 250°C (16°C / min) and then held at 250°C for 20 min. After heating to 250°C for 20 min, the films were removed from the oven "hot" and allowed to cool in air.

[0092] For E1, a polyimide solution with carbon black was prepared as described above for CE1. 1.04 g of a 10 wt % solution of Jeffamine® D-230 (Huntsman) in DMAc was added to the polymer solution prior to the final degassing step. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 30 seconds while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0093] The solutions were cast onto a matte PET substrate at 25°C to produce 1-2 mil cured films. The matte PET substrate films were heated at 80°C for 10 minutes, then lifted off the matte PET surface and mounted into an 8 x 12 inch frame. The mounted films were placed in an oven and heated as described above for CE1.

[0094] Comparative Example 2 and Example 2 For the polyamic acid (PAA) of Comparative Example 2 and Example 2 (CE2 and E2), using a monomer composition of BPADA1.0 / / PIDA1.0, 6.77 g of 3-(4-aminophenyl)-1,1,3-trimethyl-5-indanamine (PIDA, Changzhou Sunlight Pharmaceutical Co., Ltd., China) was added to a 300 ml beaker in a nitrogen purged glove box along with 180 g of DMAc. 13.20 g of 4,4'-bisphenol A dianhydride (BPADA, Sabic, Riyadh, Saudi Arabia) was added in three aliquots at three 5-10 minute intervals. The reaction mixture was held at 40°C during these additions. The reaction was held overnight at 40°C until the weight average molecular weight, Mw=284,000 g / mol, with a dispersity of 1.85 was reached.

[0095] For CE2 and E2, 9.47 g of β-picoline (Sigma Aldrich, Milwaukee, WI) and 10.38 g of acetic anhydride (Sigma Aldrich) were combined with the PAA solution to prepare a fully imidized polyimide solution (polyimideamic acid solution). The reaction mixture was stirred at 40° C. for 30 minutes and then heated to 80° C. for 3 hours to imidize the solution. 200 g of room temperature polymer solution was poured into 600 ml of methanol (Sigma Aldrich) in a blender and stirred rapidly to grind the polymer solids. The ground polymer solids were stirred in the blender for 10 minutes and then collected by filtration. The polymer was air-dried overnight and then further vacuum-dried at 35° C. overnight.

[0096] For CE2, a polyimide solution with carbon black was prepared and cast and heated to form a film as described above for CE1.

[0097] For E2, a polyimide solution with carbon black was prepared as described above for CE1. 0.77 g of a 10 wt % solution of Jeffamine® D-230 in DMAc was added to the polymer solution prior to the final degassing step. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 30 seconds while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0098] The solution was cast onto a matte PET substrate at 25° C. to produce a cured film of approximately 2.5 mils. The matte PET substrate film was heated at 80° C. for 15 minutes, then lifted off the matte PET surface and mounted into an 8×12 inch frame. The mounted film was placed in an oven and heated as described above for CE1.

[0099] Table 1 summarizes the properties of E1-E2 and CE1-CE2. Although E1-E2 and CE1-CE2 all exhibit good color and gloss properties, the crosslinked films (E1 and E2) have superior chemical resistance as demonstrated by gel fraction measurements. Furthermore, the 60GU of the crosslinked films is lower than their non-crosslinked counterparts.

[0100] [Table 1]

[0101] Comparative Example 3 In Comparative Example 3 (CE3), the Matrimid® 9725 polymer used in CE1 and E1 was used as a dry powder.

[0102] For CE3, 2.5 g of dry polymer resin was added to 8.7 g of DMAc and mixed in a centrifugal planetary mixer to obtain a solution. The solution was degassed using a centrifugal planetary mixer at 2000 rpm for 10 minutes to degas the polymer. 0.05 g of a 2.5 wt% solution of triphenyl phosphite belt release agent in DMAc and 1.25 g of a 10 wt% solution of SB4 carbon in DMAc were added to the polyimide solution. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 2 minutes, followed by degassing at 2000 rpm for 10 minutes. 1.04 g of a 10 wt% solution of Jeffamine® D-230 in DMAc was added to the polymer solution. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 30 seconds while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0103] The solutions were cast onto Mylar® polyester film (DuPont Teijin Films USA, Chester, VA) substrates at 25°C to produce 1-2 mil cured films. The films on the substrates were heated to 80°C for 15 minutes, then lifted off the polyester film surface and mounted in an 8 x 12 inch frame. The mounted films were placed in an oven and heated as described above for CE1. Casting of polyimides onto the smooth surface (low Spv) of Mylar® polyester film results in polymer films with high gloss despite their high degree of crosslinking (see Table 1).

[0104] Example 3 For the polyamic acid (PAA) solution of Example 3 (E3), using a monomer composition of CBDA 0.6 / 6FDA 0.4 / / TFMB 1.0, 2.268 kg of trifluoromethyl-benzidine (TFMB, Seika Corp., Wakayama Seika Kogyo Co., LTD., Japan) was added to a 72 L nitrogen-purged resin kettle along with 32.191 kg of DMAc. 1.252 kg of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA, Daikin America Incorporated, Decatur, AL), and 0.829 kg of cyclobutane dianhydride (CBDA, Wilshire Technologies, Princeton, NJ) were added in three aliquots at three 60 minute intervals. The reaction mixture was held at 40°C during these additions. A small amount of 6FDA powder was added to polymerize ("complete") the polymer to 12 poise.

[0105] For E3, an additional 2.787 kg of DMAc was added and stirred for 60 minutes to prepare a fully imidized polyimide solution (polyimide amide acid solution). 1.65 kg of β-picoline and 1.808 kg of acetic anhydride were combined with the PAA solution. The reaction mixture was heated to 80° C. for 2 hours to imidize the solution. 1,000 g of room temperature polymer solution was poured into 2 L of methanol in a blender and stirred rapidly to grind the polymer solids. The ground polymer solids were collected by filtration after stirring in the blender for 10 minutes. The polymer was air-dried overnight and then further vacuum-dried at 50° C. overnight.

[0106] For E3, 2.5 g of dried polymer was added to 21.2 g of DMAc and mixed in a centrifugal planetary mixer to obtain a solution. The solution was degassed using a centrifugal planetary mixer for 10 minutes at 2000 rpm to degas the polymer. 0.05 g of a 2.5 wt% solution of triphenyl phosphite belt release agent in DMAc and 1.25 g of a 10 wt% solution of SB4 carbon in DMAc were added to the polyimide solution. This solution was mixed using a centrifugal planetary mixer for 2 minutes at 2200 rpm. 0.5 g of a 10 wt% solution of Jeffamine® D-230 in DMAc was added to the polymer solution. The solution was mixed using a centrifugal planetary mixer for 30 seconds at 2200 rpm while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0107] The solutions were cast onto matte PET substrates at 25° C. to produce 1-2 mil cured films as described above for CE1.

[0108] Example 4 For the polyamic acid (PAA) solution of Example 4 (E4), using a monomer composition of BPADA 1.0 / / 3,4-ODA 1.0, 5.56 g of 3,4-oxydiphenylamine (3,4-ODA, Wakayama Seika Kogyo Co., LTD., Japan) was added to a 300 ml beaker in a nitrogen-purged glove box along with 180 g of DMAc. 14.415 g of BPADA was added in three aliquots at three 5-10 min intervals. The reaction mixture was held at 40° C. overnight during these additions. The reaction was held at 40° C. until the weight average molecular weight, Mw=184,000 g / mol, and dispersity of 2.00 was reached.

[0109] For E4, 10.34 g of β-picoline and 11.33 g of acetic anhydride were combined with the PAA solution to prepare a fully imidized polyimide solution (polyimide amic acid solution). The reaction mixture was stirred at 40° C. for 30 minutes and then heated to 80° C. for 3 hours to imidize the solution. 200 g of room temperature polymer solution was poured into 600 ml of methanol in a blender and rapidly stirred to grind the polymer solids. The ground polymer solids were stirred in the blender for 10 minutes and then collected by filtration. The polymer was air-dried overnight and then further vacuum-dried at 35° C. overnight.

[0110] For E4, 2.5 g of dried polymer was added to 8.7 g of DMAc and mixed in a centrifugal planetary mixer to obtain a solution. The solution was degassed using a centrifugal planetary mixer for 10 minutes at 2000 rpm to degas the polymer. 0.05 g of a 2.5 wt% solution of triphenyl phosphite belt release agent in DMAc and 1.25 g of a 10 wt% solution of SB4 carbon in DMAc were added to the polyimide solution. The solution was mixed using a centrifugal planetary mixer for 2 minutes at 2200 rpm. 0.42 g of a 10 wt% solution of Jeffamine® D-230 in DMAc was added to the polymer solution. The solution was mixed using a centrifugal planetary mixer for 30 seconds at 2200 rpm while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0111] The solutions were cast onto matte PET substrates at 25° C. to produce 1-2 mil cured films as described above for CE1.

[0112] Example 5 For the polyamic acid (PAA) solution of Example 5 (E5), using a monomer composition of BPADA 1.0 / / RODA 1.0, 8.647 g of 1,3-bis(4-aminophonoxy)benzene (RODA) was added to a 300 ml beaker in a nitrogen purged glove box along with 180 g of DMAc. 8.630 g of BPADA was added in smaller aliquots and stirred until completely dissolved. The reaction mixture was held at 40° C. during these additions. The reaction was held overnight at 40° C. until the weight average molecular weight, Mw=184,000 g / mol, dispersity of 2.00 was reached.

[0113] In E5, an additional 17.0 g of DMAc was added to the PAA solution along with 10.31 g of β-picoline and 11.31 g of acetic anhydride to prepare a fully imidized polyimide solution (polyimideamic acid solution). The reaction was stirred at room temperature for approximately 2 hours. During this time, the viscosity of the solution increased slightly and an additional 50 ml of DMAC was added. The solution was allowed to continue stirring overnight.

[0114] 200 g of the polymer solution was mixed with approximately 600 ml of methanol in a laboratory blender until fine solid particles were produced. The resulting suspension was then filtered, air-dried at room temperature overnight, and vacuum-dried at 50° C. overnight.

[0115] For E5, 2.5 g of dried polymer was added to 12.9 g of DMAc and mixed in a centrifugal planetary mixer to obtain a solution. The solution was degassed using a centrifugal planetary mixer for 10 minutes at 2000 rpm to degas the polymer. 0.05 g of a 2.5 wt% solution of triphenyl phosphite belt release agent in DMAc and 1.25 g of a 10 wt% solution of SB4 carbon in DMAc were added to the polyimide solution. This solution was mixed using a centrifugal planetary mixer for 2 minutes at 2200 rpm. 0.42 g of a 10 wt% solution of Jeffamine® D-230 in DMAc was added to the polymer solution. The solution was mixed using a centrifugal planetary mixer for 30 seconds at 2200 rpm while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0116] The solutions were cast onto matte PET substrates at 25° C. to produce 1-2 mil cured films as described above for CE1.

[0117] Example 6 In Example 6 (E6), the Matrimid® 9725 polymer used in CE1 and E1 was used as a dry powder.

[0118] For E6, 2.5 g of dried polymer resin was added to 8.7 g of DMAc and mixed in a centrifugal planetary mixer to obtain a solution. The solution was degassed using a centrifugal planetary mixer at 2000 rpm for 10 minutes to degas the polymer. 0.05 g of a 2.5 wt% solution of triphenyl phosphite belt release agent in DMAc and 1.25 g of a 10 wt% solution of SB4 carbon in DMAc were added to the polyimide solution. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 2 minutes, followed by degassing at 2000 rpm for 10 minutes. 2.08 g of a 10 wt% solution of Jeffamine® D-230 in DMAc was added to the polymer solution. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 30 seconds while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0119] The solutions were cast onto matte PET substrates at 25° C. to produce 1-2 mil cured films as described above for CE1.

[0120] Example 7 In Example 7 (E7), the Matrimid® 9725 polymer used in CE1 and E1 was used as a dry powder.

[0121] For E7, 2.5 g of dry polymer resin was added to 8.7 g of DMAc and mixed in a centrifugal planetary mixer to obtain a solution. The solution was degassed using a centrifugal planetary mixer at 2000 rpm for 10 minutes to degas the polymer. 0.05 g of a 2.5 wt% solution of triphenyl phosphite belt release agent in DMAc and 1.25 g of a 10 wt% solution of SB4 carbon in DMAc were added to the polyimide solution. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 2 minutes, followed by degassing at 2000 rpm for 10 minutes. 0.66 g of a 10 wt% solution of Jeffamine® T-403 (Huntsman) in DMAc was added to the polymer solution. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 30 seconds while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0122] The solutions were cast onto matte PET substrates at 25° C. to produce 1-2 mil cured films as described above for CE1.

[0123] Example 8 In Example 8 (E8), the Matrimid® 9725 polymer used in CE1 and E1 was used as a dry powder.

[0124] For E8, 2.5 g of dry polymer resin was added to 8.7 g of DMAc and mixed in a centrifugal planetary mixer. The solution was degassed using a centrifugal planetary mixer at 2000 rpm for 10 minutes to degas the polymer. 0.05 g of a 2.5 wt% solution of triphenyl phosphite belt release agent in DMAc and 1.25 g of a 10 wt% solution of SB4 carbon in DMAc were added to the polyimide solution. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 2 minutes, followed by degassing at 2000 rpm for 10 minutes. 0.31 g of a 10 wt% solution of m-xylylenediamine (MXD, Sigma Aldrich, Milwaukee, WI) in DMAc was added to the polymer solution. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 30 seconds while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0125] The solutions were cast onto matte PET substrates at 25° C. to produce 1-2 mil cured films as described above for CE1.

[0126] Example 9 In Example 9 (E9), the Matrimid® 9725 polymer used in CE1 and E1 was used as a dry powder.

[0127] For E9, 2.5 g of dry polymer resin was added to 4.95 g of DMAc and mixed in a centrifugal planetary mixer to obtain a solution. The solution was degassed using a centrifugal planetary mixer for 10 minutes at 2000 rpm to degas the polymer. 0.05 g of a 2.5 wt % solution of triphenyl phosphite belt release agent in DMAc and 5 g of a 10 wt % solution of perylene black (Paliogen® Black L0086, BASF SE, Germany) in DMAc were added to the polyimide solution. The solution was mixed using a centrifugal planetary mixer for 2 minutes at 2200 rpm, followed by degassing for 10 minutes at 2000 rpm. 1.04 g of a 10 wt % solution of Jeffamine® D-230 in DMAc was added to the polymer solution. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 30 seconds while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0128] The solutions were cast onto matte PET substrates at 25° C. to produce 1-2 mil cured films as described above for CE1.

[0129] Example 10 In Example 10 (E10), the Matrimid® 9725 polymer used in CE1 and E1 was used as a dry powder.

[0130] For E10, 2.5 g of dry polymer resin was added to 7.45 g of DMAc and mixed in a centrifugal planetary mixer to obtain a solution. The solution was degassed using a centrifugal planetary mixer for 10 minutes at 2000 rpm to degas the polymer. 0.05 g of a 2.5 wt % solution of triphenyl phosphite belt release agent in DMAc, 1.25 g of a 10 wt % solution of SB4 carbon in DMAc, and 1.25 g of a 10 wt % solution of silica matting agent (Syloid® C807, W.R. Grace & Co., Columbia, MD) in DMAc were added to the polyimide solution. The solution was mixed using a centrifugal planetary mixer for 2 minutes at 2200 rpm, followed by degassing for 10 minutes at 2000 rpm. 1.04 g of a 10 wt % solution of Jeffamine® D-230 in DMAc was added to the polymer solution. The solution was mixed using a centrifugal planetary mixer at 2200 rpm for 30 seconds while cooling in a cold cup, followed by degassing at 2000 rpm for 5 minutes and holding at cold temperature.

[0131] The solutions were cast onto matte PET substrates at 25°C to produce 1-2 mil cured films as described above for CE1. As summarized in Table 2, E3-E10 demonstrate a range of crosslinked polymers with low refractive index and low color and gloss for films with sufficient surface roughness.

[0132] Comparative Example 4 For the polyamic acid solution of Comparative Example 4 (CE4), using a monomer composition of BPDA 1.0 / / PPD 1.0, 10.95 g of p-phenylenediamine (PPD) was added to a 300 ml nitrogen purged reaction vessel along with 160.17 g of anhydrous DMAc. 28.89 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added over several minutes. The reaction mixture was stirred until all monomers had reacted. The overall stoichiometric ratio of dianhydride to diamine was approximately 0.97:1. The mixture achieved a polymer viscosity of 75-250 poise at approximately 20% polyamic acid solids. The polymer was polymerized ("Complete") to increase molecular weight and a small amount of PMDA solution in DMAc was added to obtain the target viscosity. The polymer solution was stored in the freezer until use.

[0133] A solution was prepared by adding 8.42 g of a 10 wt % solution of SB4 carbon in DMAc to 91.58 g of the polymer solution and mixed in a centrifugal planetary mixer. The solution was cast onto a matte PET substrate at 25°C to produce a 1-2 mil cured film. The film on the matte PET substrate was heated at 90°C for 20 minutes, then lifted off the matte PET surface and mounted in an 8 x 12 inch frame. The mounted film was placed in an oven. The oven was heated from 120 to 320°C (16°C / min), then the film was removed from the oven "hot" and placed in another oven at 400°C for 5 minutes, after which it was removed and cooled in air.

[0134] Comparative Example 5 For the polyamic acid solution of Comparative Example 5 (CE5), using a monomer composition of ODPA0.5 / PMDA0.5 / MPD0.5 / BAPP0.5, 20.48 g of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) and 5.40 g of m-phenylenediamine (MPD) were added to a 300 ml nitrogen purged reaction vessel along with 148.2 g of DMAc. 10.45 g of pyromellitic dianhydride (PMDA) and 15.48 g of 4,4'-oxydiphthalic anhydride (ODPA) were added over several minutes. The reaction mixture was stirred until all monomers had reacted. The overall stoichiometric ratio of dianhydride to diamine was approximately 0.98:1. The mixture achieved a polymer viscosity of 75-250 poise at approximately 26% polyamic acid solids. The polymer was polymerized ("Complete") to increase molecular weight and to obtain the target viscosity by adding small amounts of a solution of PMDA in DMAc. The polymer solution was stored in the freezer until use.

[0135] A solution was prepared by adding 11.84 g of a 10 wt% solution of SB4 carbon in DMAc to 88.64 g of the polymer solution and mixed in a centrifugal planetary mixer. The solution was cast onto a matte PET substrate at 25°C to produce a 1-2 mil cured film. The matte PET substrate film was heated at 90°C for 20 minutes, then lifted off the matte PET surface and mounted in an 8 x 12 inch frame. The mounted film was placed in an oven. The oven was heated from 120 to 350°C (16°C / min), then the film was removed from the oven "hot" and allowed to cool in air. As summarized in Table 2, CE4 and CE5 demonstrate the challenge of achieving both low color and low gloss in a single layer polymer film when the refractive index is too high, CE4, or when the surface roughness is too low, CE5.

[0136] [Table 2]

[0137] It should be noted that not all of the acts set forth above in the general description are required, that some of the specific acts may not be required, and that additional acts may be performed in addition to those described. Furthermore, the order in which each of the acts are listed is not necessarily the order in which they are performed. After reading this specification, one of ordinary skill in the art will be able to determine which acts can be used for their particular needs or desires.

[0138] In the foregoing specification, the present invention has been described with reference to specific embodiments. However, those skilled in the art will appreciate that various modifications and changes can be made without departing from the scope of the present invention as set forth in the following claims. All features disclosed in this specification may be replaced by alternative features serving the same, equivalent or similar purpose.

[0139] Accordingly, the specification is to be regarded in an illustrative rather than a restrictive sense, and all such modifications are intended to be included within the scope of the present invention.

[0140] Benefits, other advantages, and solutions to problems have been described above with respect to certain embodiments. However, these benefits, advantages, solutions to problems, and any elements that may cause or make any benefit, advantage, or solution more noticeable should not be construed as a critical, required, or essential feature or element of any or all of the claims.

Claims

1. 60 to 99 weight percent crosslinked polyimide having a gel fraction in the range of 20 to 100% and a refractive index of 1.74 or less; 1 to 40% by weight of a colorant; A monolayer polymer film comprising: The surface of said monolayer polymer film is textured and has a maximum roughness (Spv) of 6 μm or more, an L* color of 30 or less, and a 60° gloss of 15 or less.

2. 10. The monolayer polymeric film of claim 1 further comprising a matting agent.

3. A printed circuit board coverlay comprising the monolayer polymeric film of claim 1.

Citation Information

Patent Citations

  • Method for manufacturing resin film and light-shielding film

    JP2010149334A

  • Black heat-resistant light-blocking film, method for producing the same, and aperture stop, light quantity adjusting module and heat-resistant light-blocking tape each using the black heat-resistant light-blocking film

    JP2011128598A

  • Matte finish polyimide film and related methods

    JP2013501850A

  • Pigment-added polyimide film

    JP2014141575A

  • Black polyimide film

    JP2016047863A